TARGET PLANNING IN THE CONTEXT OF MANAGEMENT OF THEIR FINANCIAL DEVELOPMENT - B. V. Samorodov (Стратегические решения и риск-менеджмент)
In the paper the mathematical model of optimization tasks of the bank activity financial indicators is built with the purpose of increase of their values to standard and with the purpose increase of concrete bank rating in general rating at comparison with banks-competitors. The tasks are set as the classic tasks of the nonlinear programming with nonlinear functional and possible nonlinear constraints.